Acute Pesticide Poisoning: Review of Patients Attending at Emergency Department in Chitwan Medical College - Lamsal, Daya Ram (Journal of Chitwan Medical College, 2013)
To find out the hospital based incidence, pattern and fatality of acute pesticide poisoning which may be helpful to develop better management strategy and preventive campaign. A total of 88 patients were reported in emergency with acute pesticide poisoning out of 178 total acute poisoning cases resulting in APP rate 49.43% of total poisoning cases. Male: Female ratio was 1:1.5. The age group specific incidence of acute poisoning showed 7.95% in 0-14 years, 45.55% in 15-29 years 30.68% in 30-44 years and 12.50% in 45-59 years and3.40% in 60 years and above. Out of 88 patients 79.55% admitted,20.45% of patient status was unknown as these patients were referred or refused admission. lost follow up .Among admitted patients 8.57% died and 91.43% dischared from hospital. Maximum case fatality ratio (28.57%) was due to endosulfan poisoning. Pesticide is responsible in 49.43% of all poisoning patients visiting to emergency department with the mortality of 6.80% among pesticide poisoning, Women have high morbidity but man predominantly exceeds on mortality rate.. Highest case fatality observed among the endosufan exposed group. How patients are getting such toxic poisons and why these victims are being exposed needs further study. Emphasis on case management and preventive campaigns would have some impact in reducing morbidity and mortality from acute pesticide poisoning. Journal of Chitwan Medical College 2013; 3(1): 62-64 DOI: http://dx.doi.org/10.3126/jcmc.v3i1.8469